Exploring the Therapeutic Potential of Bixa orellana L. Phytochemicals in Oxidative Stress and Complications using Network Pharmacology - Akthar, Wasim; Ekbbal, Rustam; Sharma, Himanchal (Current Bioactive Compounds, 2025)
IntroductionThis study explores the therapeutic potential of Bixa orellana (B. orellana), focusing on its bioactive compounds and antioxidant effects. Phytochemical analysis combined with network pharmacology was employed to investigate its multi-targeted therapeutic potential against oxidative stress.MethodsThe antioxidant activity of B. orellana flower extract was determined using DPPH assays. High-performance thin-layer chromatography (HPTLC) and liquid chromatography-mass spectrometry (LC-MS) were performed to profile key bioactive constituents. Network pharmacology analysis linked to these phytochemicals was performed to determine its role in oxidative stress and associated complications.ResultsThe results showed a significant DPPH activity of the flower extract of B. orellana. HPTLC profiling showed several major and minor metabolites at different Rf values, while LC-MS profiling revealed quercetin, kaempferol, genestin, etc. as key components of the flower extract. In network pharmacology analysis, quercetin showed a significant interaction with genes like TP53, NOS2, and CAT, while kaempferol targeted SOD2 and NFE2L2, both crucial in oxidative stress regulation. The results highlight the multi-targeted approach of B. orellana flower extract compounds in modulating oxidative stress pathways.ConclusionThis comprehensive approach revealed multiple molecular pathways influenced by B. orellana compounds, providing a strong foundation for their therapeutic potential in oxidative stress-related diseases.
Keywords: phytochemical analysis